Sustainable Paving Blocks from Fly Ash: An Innovation for the SDGs - Wibowo, Sekarsari; Cahyono, Luqman; Khaqiqi, Alwi Sina; Rahayuningsih, Siti; Al Hazman, Muhammad; Kusuma, Dwi Mahendra; Ridwansyah, Moh. Farikh Tirta (Civil and Environmental Science Journal (CIVENSE), 2025)
This study determined the optimal proportion of fly ash as a partial replacement for Portland cement in paving block mixtures to maximize compressive strength while supporting sustainability. Three fly ash substitution levels (10%, 20%, and 30% by cement weight) were evaluated. All mixtures met the K-300 standard (≥30.6 MPa), but the 20% substitution proved optimal, yielding the highest average compressive strength of 37.2 MPa with the lowest variation (CoV of 5.8%). The incorporation of fly ash also enhanced physical properties by reducing water absorption and porosity. The findings validate the use of fly ash for producing high-performance, environmentally friendly paving blocks that meet stringent quality standards.